LncRNA HOTAIR down-expression inhibits the invasion and tumorigenicity of epithelial ovarian cancer cells by suppressing TGF-β1 and ZEB1 - Yufu Zhou; Yunjie Zhang; Yidan Shao; Xiaoli Yue; Yifan Chu; Cuiping Yang; Dengyu Chen (Discover Oncology, 2023)
Abstract Background Epithelial ovarian cancer (EOC) is a pathological type with a higher mortality rate among gynecological cancers today. Long-chain noncoding RNAs (lncRNAs) can regulate the transcription and expression of cellular genes. However, the downstream molecules regulated by lncRNA HOTAIR have not been well studied. The effects of downregulated lncRNA HOTAIR on EOC invasiveness and tumorigenicity in nude mice, along with TGF- β1 and ZEB1 in epithelial ovarian cancer cells, need to be investigated in further research. Results RT-qPCR was used to detect lncRNA HOTAIR and TGF-β1 and ZEB1 mRNA expression in EOC SKOV3 cells. The expression of lncRNA HOTAIR in SKOV3 cells transfected with the recombinant shHOTAIR interference plasmid was significantly lower than that of the negative control. Compared with the negative control, the matrix gel invasion ability of shHOTAIR SKOV3 cells in vitro and their tumorigenicity in nude mice were significantly reduced. Moreover, compared with the control, the expression of ZEB1 protein in shHOTAIR-SKOV3 xenograft tumors was significantly reduced. Downregulation of lncRNA HOTAIR expression significantly reduced TGF-β1 and ZEB1 mRNA expression, but increased the expression of E-cadherin mRNA. In summary, downregulated lncRNA HOTAIR in EOC SKOV3 cells transfected with shHOTAIR can inhibit TGF-β1, reduce ZEB1, increase E-cadherin, and significantly reduce the invasiveness and tumorigenicity of ovarian epithelial cancer SKOV3 cells. Conclusions These results suggest that the lncRNA HOTAIR may be an effective target for the treatment of human EOC.